(untitled) - Means, Jan (San Francisco, 2005)
Step by step, Facilitating the Project Lifecycle guides the project manager/facilitator in making smart choices about when and how to pull key talent together to spell success for the project and ultimately the organization. The authors will help you understand the benefits of using facilitated group work sessions to get real work done during a project and get it done better and more efficiently than more traditional individual work approaches.
Keywords: Project management,Group facilitation,Quản lý dự án,Tập đoàn thuận lợi